Upaya Guru Pendidikan Agama Islam Dalam Mengatasi Kenakalan Peserta Didik di SMK Negeri 1 Payung - Rudini, Rudini; Purnomo, Fazrul Sandi; Maryana, Maryana (LENTERNAL: Learning and Teaching Journal, 2022)
This research raises the issue of the efforts of Islamic Religious Education teachers in overcoming the acquaintance of students at SMK Negeri 1 Payung. Based on initial observations that have been made, SMK Negeri 1 Payung has a set of rules that can bind the behavior of students at school. However, in reality, it is not as expected; students still carry out activities that should not be done, such as smoking, skipping class, and not obeying the rules that the school has made. The method used in this research is field research. The results obtained indicate that the teacher has made efforts to overcome the delinquency of students, such as preventive action, repressive action, and curative and rehabilitation actions. The conclusion obtained is that the form of juvenile delinquency at SMK Begeri 1 Payung can cause physical victims and status violations. Causal factors consist of internal and external factors.